Forecasting the commune income as a determinant of local sustainable development - Marciniuk-Kluska, Anna (Management and Administration Journal, 2019)
At the present time it is difficult to overcome problems with research in sustainable local devel-opment due to their diversity and the large-scale social and economic changes in development conditions. The complexity and significance of issues connected with local development assessment require a comprehensive and methodological approach which can form grounds for planning desirable events and shaping the future condition of local government units. Changes taking place in the competitive environment conditions reveal the need for a consistent, prospective and effective attitude to local processes and defining the main directions of development. Planning the development at the local level is inevitable owing to the necessity of optimising budget expenses and performing public tasks properly. The purpose of the paper is to present a forecast of the rural commune income in 2018-2020 The data from 2003-2016 (GUS) was used in order to prepare rural commune income and expenditure forecasts for 2018-2020. The level of budgetary in-come and expenditure and the increment of the smoothed variable representing the linear trend coefficient were subject to exponential smoothing. The local government units subject to the analysis are very diversified, often char-acterised by large-scale development gaps and low attractiveness of location; the situation is most difficult in rural areas.